Iyá Mìn: resistance processes based on the ancestral knowledge of the Yabás in the Boca 07 Collective (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article presents Afro-referenced approaches to the processes of creation, resistance, and identity affirmation of the Boca 07 Collective. Based on Afro-Brazilian dances and the ancestral knowledge of the Yabás, the collective built an artistic practice that challenges religious racism, intolerance, and institutional erasure, articulating art and spirituality as forms of resistance. From an autoethnographic and performative methodological perspective, the research proposed a reflection on the body as a territory of memory, ritual, and insurgency, in dialogue with Afro-diasporic and decolonial epistemologies in the Undergraduate Program in Dance.
Keywords: Afro-Brazilian dance; ancestral knowledge; performance; religious intolerance; cultural resistance